RNAseq based transcriptomics study of SMCs from carotid atherosclerotic plaque: BMP2 and IDs proteins are crucial regulators of plaque stability - Alloza, Iraide; Goikuria, Haize; Idro, Juan Luis; Triviño, Juan Carlos; Fernández Velasco, José María; Elizagaray, Elena; García-Barcina, María; Montoya-Murillo, Genoveva; Sarasola, Esther; Vega Manrique, Reyes; Freijo, Maria del Mar; Vandenbroeck, Koen (Scientific reports, 2017)
Carotid artery atherosclerosis is a risk factor to develop cerebrovascular disease. Atheroma plaque can become instable and provoke a cerebrovascular event or else remain stable as asymptomatic type. The exact mechanism involved in plaque destabilization is not known but includes among other events smooth muscle cell (SMC) differentiation. The goal of this study was to perform thorough analysis of gene expression differences in SMCs isolated from carotid symptomatic versus asymptomatic plaques. Comparative transcriptomics analysis of SMCs based on RNAseq technology identified 67 significant differentially expressed genes and 143 significant differentially expressed isoforms in symptomatic SMCs compared with asymptomatic. 37 of top-scoring genes were further validated by digital PCR. Enrichment and network analysis shows that the gene expression pattern of SMCs from stable asymptomatic plaques is suggestive for an osteogenic phenotype, while that of SMCs from unstable symptomatic plaque correlates with a senescence-like phenotype. Osteogenic-like phenotype SMCs may positively affect carotid atheroma plaque through participation in plaque stabilization via bone formation processes. On the other hand, plaques containing senescence-like phenotype SMCs may be more prone to rupture. Our results substantiate an important role of SMCs in carotid atheroma plaque disruption.